Research on the Collaborative Language Application Ability of Learning Task Cluster from the Perspective of Cultural Tool Theory - Wu, Peng (Journal of Educational Research and Policies, 2025)
The current implementation of Chinese language learning task cluster faces integration challenges, with the root cause being cultural disconnection that weakens linguistic competence foundations and systemic barriers hindering dynamic symbol circulation, leading to risks of linguistic competence dilution. Although competency-oriented curriculum standards have gained widespread recognition, achieving a comprehensive leap from singular language skills to integrated literacy and from instrumental rationality to value-based rationality remains unbroken through. This study employs cultural instrument theory as a breakthrough mechanism, critically revealing how “de-culturalization” training and “inter-group isolation” obscure the essence of language-cultural mediation. Building on Vygotsky’s mediating theory and Engestrom’s activity theory, it reconstructs the three-dimensional attributes of language “instrument-culture-practice” and the collaborative core of task clusters characterized by “contradictory drive and hierarchical progression.” The core insight lies in elucidating their linkage mechanism through tool circulation and meaning proliferation, driving holistic advancement of linguistic competence across cognitive proficiency, cultural negotiation capabilities, and symbolic mastery. Ultimately transcending the trap of instrumental rationality, this study advocates constructing a dialectical paradigm of “instrument-subject-culture”, guiding students to transition from skill users to cultural producers and identity awakeners, thereby providing practical pathways for implementing core competencies.